The Effect Of Wet Cupping On The Explosive Power Of Volleyball Players - Ouali Abdennour (sports creativity, 2025)
Nowadays, the world witnesses rapid development in various sports; the sports achievements and the high level of sports in general did not come over night, but it has been the result of well planning for sports training, which was based mainly on research, expertise and scientific experiments. Despite the scientific and technical progress of modern therapeutic and medical methods, the methods of folk medicine, including wet cupping, are still practiced in many societies to the present time, either for their therapeutic efficiency in dealing with many cases of illness or prevention of infection. Besides, the use of wet cupping by champions in the Rio Olympics competition raised a wave of questions about the benefits of alternative medicine methods, which is adopted by the most powerful athletes in the world (Michael Phillips, Alex Nadour). Sports cupping is a legal regulation of the applications of cupping with athletes in several areas such as first aid, rehabilitation and quick recovery and energy. The most common cupping types used in sport are: bloody cupping (wet), dry cupping, and rub-down cupping. The objective of the research is to uncover the effect of wet cupping on the explosive power of the arms and legs of the volleyball senior players. In the light of the results and their discussion, the researcher concludes that the tests are far superior in the post-test results of explosive power of the arms and legs in the study sample.